Four‐dimensional respiratory motion‐resolved whole heart coronary MR angiography. Issue 4 (28th March 2016) - Piccini, Davide; Feng, Li; Bonanno, Gabriele; Coppo, Simone; Yerly, Jérôme; Lim, Ruth P.; Schwitter, Juerg; Sodickson, Daniel K.; Otazo, Ricardo; Stuber, Matthias
Abstract : Purpose: Free‐breathing whole‐heart coronary MR angiography (MRA) commonly uses navigators to gate respiratory motion, resulting in lengthy and unpredictable acquisition times. Conversely, self‐navigation has 100% scan efficiency, but requires motion correction over a broad range of respiratory displacements, which may introduce image artifacts. We propose replacing navigators and self‐navigation with a respiratory motion‐resolved reconstruction approach. Methods: Using a respiratory signal extracted directly from the imaging data, individual signal‐readouts are binned according to their respiratory states. The resultant series of undersampled images are reconstructed using an extradimensional golden‐angle radial sparse parallel imaging (XD‐GRASP) algorithm, which exploits sparsity along the respiratory dimension. Whole‐heart coronary MRA was performed in 11 volunteers and four patients with the proposed methodology. Image quality was compared with that obtained with one‐dimensional respiratory self‐navigation. Results: Respiratory‐resolved reconstruction effectively suppressed respiratory motion artifacts. The quality score for XD‐GRASP reconstructions was greater than or equal to self‐navigation in 80/88 coronary segments, reaching diagnostic quality in 61/88 segments versus 41/88. Coronary sharpness and length were always superior for the respiratory‐resolved datasets, reaching statistical significance ( P < 0.05) in most cases. Conclusion: XD‐GRASP represents an attractive alternative for handling respiratory motion in free‐breathing whole heart MRI and provides an effective alternative to self‐navigation. Magn Reson Med 77:1473–1484, 2017. © 2016 International Society for Magnetic Resonance in Medicine